Pharmacotherapy for behavioural manifestations in frontotemporal dementia: An expert consensus from the European Reference Network for Rare Neurological Diseases (ERN-RND) - Wittebrood, Casper; Boban, Marina; Cagnin, Annchiara; Capellari, Sabina; De Winter, François-Laurent; Djamshidian, Atbin; González, Manuel Menéndez; Hjermind, Lena E; Krajcovicova, Lenka; Krüger, Johanna; Levin, Johannes; Reetz, Kathrin; et al. (European journal of neurology, 2024)
BACKGROUND AND PURPOSE: Frontotemporal dementia (FTD) is a neurodegenerative disorder characterized by pervasive personality and behavioural disturbances with severe impact on patients and caregivers. In current clinical practice, treatment is based on nonpharmacological and pharmacological approaches. Unfortunately, trial-based evidence supporting symptomatic pharmacological treatment for the behavioural disturbances in FTD is scarce despite the significant burden this poses on the patients and caregivers. METHOD: The study examined drug management decisions for several behavioural disturbances in patients with FTD by 21 experts across European expert centres affiliated with the European Reference Network for Rare Neurological Diseases (ERN-RND). RESULTS: The study revealed the highest consensus on drug treatments for physical and verbal aggression, impulsivity and obsessive delusions. Antipsychotics (primarily quetiapine) were recommended for behaviours posing safety risks to both patients and caregivers (aggression, self-injury and self-harm) and nightly unrest. Selective serotonin reuptake inhibitors were recommended for perseverative somatic complaints, rigidity of thought, hyperphagia, loss of empathy and for impulsivity. Trazodone was specifically recommended for motor unrest, mirtazapine for nightly unrest, and bupropion and methylphenidate for apathy. Additionally, bupropion was strongly advised against in 10 out of the 14 behavioural symptoms, emphasizing a clear recommendation against its use in the majority of cases. CONCLUSIONS: The survey data can provide expert guidance that is helpful for healthcare professionals involved in the treatment of behavioural symptoms. Additionally, they offer insights that may inform prioritization and design of therapeutic studies, particularly for existing drugs targeting behavioural disturbances in FTD.
Keywords: vzácné nemoci; Rare Diseases; Aggression; Consensus; Impulsive Behavior; frontotemporální demence; lidé; Europe; selektivní inhibitory zpětného vychytávání serotoninu; agrese; Evropa; antipsychotika; Antipsychotic Agents; Selective Serotonin Reuptake Inhibitors; Frontotemporal Dementia; konsensus; impulzivní chování; Humans